Effect of erosion corrosion with different fluids mechanism - Siti Nor Hafizah , Mohd Sapawi (2012)
ErosiOfl-c01T05i0fl is an important aspect of durability for materials used in the oil sands industry. The combination of a corrosive fluid and high volume of sand means that erosion, corrosion and their synergistic interactions all act to accelerate material damage. This paper presents the results of erosion corrosion on stainless steel with three different slurry which are 3.5% NaCl, seawater and water with the presence of sand. The studies of erosion corrosion with different fluids mechanism have been study by using electrochemical process. Stainless steel is used because of its higher strength and corrosion resistance: Surface roughness and corrosion rate of the specimen were determined in this experiment. By using electrochemical test, polarisation study was carried out to investigate the electrochemical corrosion behaviour of stainless steel in three different slurries. With the presence of 10% wt of sand, the solution was maintaned at constant temperature and constant velocity. A constant potential scan rate of 20 mV/s was used in all experiments. The corrosion rates of the specimen were determined from polarisation curve using Tafel extrapolation method. Surface roughness of the specimen was measured before and after the corrosion test has been done. At the end of the experiment, the erosion corrosion is acted more on specimen with seawater slurry followed by water and 3.5% NaCl. This result are influenced by high quantity of chloride ion contain in the seawater.